What can dietary patterns tell us about the Caribbean nutrition transition?. (13th November 2019) - Colombet, Z; Allès, B; Perignon, M; Landais, E; Martin-Prével, Y; Amiot-Carlin, M-J; Darmon, N; Méjean, C
Abstract: Background: Given the public health urgency facing the increasing rates of obesity and chronic diseases in the Caribbean, characterization of the nutrition transition and population groups at higher nutritional risk is needed. We identified dietary patterns in the French West Indies (FWI) and their association with individual characteristics. Methods: This cross-sectional analysis included 1, 144 Guadeloupeans and Martinicans from a representative survey. To identify dietary patterns, principal component analysis was performed using 25 food groups, followed by a clustering procedure classifying subjects in independent clusters. Their associations with health status, Diet Quality Index-International (DQI-I), food supply behaviors, sociodemographic and economic characteristics were studied using multivariable models. Results: Four dietary patterns were identified, representing 25%, 24%, 31% and 20% of the sample: (1) a "healthy" cluster characterised by a high DQI-I, composed of high educated individuals; (2) a "traditional" cluster with a high DQI-I and high intakes of traditional dishes, formed mostly by women and older persons, with a high obesity prevalence (26%); (3) a "western" cluster with a low DQI-I, high intakes of sweetened beverages, snacks and fast foods, composed mainly of young subjects, buying their fruits, vegetables and tubers only or mainly in supermarkets; and (4) a "transitional" cluster with high intakes of bread, processed meat, sauces, alcoholic and sweetened beverages but conversely high intakes of tubers, legumes, fish and low intakes of biscuits and cakes, formed mainly by middle age men, self-employed or manual workers, and 35% had metabolic syndrome. Conclusions: The dietary patterns identified reflect different steps of dietary change as described by Popkin, suggesting an ongoing nutrition transition in the FWI. This characterization provides useful information for public health actions regarding population groups at higher nutritional risk. Key messages: Four diversified dietary patterns were identified suggesting an ongoing nutrition transition in the French West Indies. Demographic and socioeconomic characteristics associated with dietary patterns, especially age, reflecting a generational contrast, provided needed information to guide future public health measures.